The Dialogical, The Ecological and Beyond - Jon Goodbun; Ben Sweeting (Footprint)
In this article Jon Goodbun and Ben Sweeting engage in a conversation about design and its complex relation to communication. They look at the role of dialogue, the dialogical (signifying signs), and the limitations of the dialogical as one considers contemporary processes of cybernetisation and how “asignifying signs” are produced and exchanged within complex systems of all kinds. Prompted by the opening question referring to cybernetics as a general study of information processes, focusing on the production, exchange, and consumption of meaning, not limited to a focus on digital logic, Goodbun and Sweeting revisit a plethora of positions on dialogue including those of Gordon Pask, Gregory Bateson, Ranulph Glanville, David Bohm among others. In so doing, they make clear certain semantic confusions related to terms such as communication vs. conversation, dialogue vs. discussion, and analogue vs. digital, and provide a richer understanding of why these semantic revisions are necessary for the context of everyday design practice. Using examples from their own research and teaching work, they point towards models where an alternative approach to communication that critically acknowledges the complications related to “asignifying signs” can help designers grapple with the ecological crisis in the contexts of politics, research, and education.